Selection of processing parameters for conversion coatings on high-strength aluminium alloys by cyclic voltammetry - Kwiatkowski, L.; Grobelny, M.; Konarski, P. (Фізико-хімічна механіка матеріалів, 2014)
A method of recording copper enrichment on AA2000 series alloys by means of cyclic voltammetry in borate buffer preceded by immersion of the samples in 0.6 M NaCl solution is extended to the assessment of various surface treatments like alkaline cleaning, desmutting, phosphating and also inorganic and organic corrosion inhibitors. Since the height of the peak determined from voltammograms results from Cu/Cu+ charge transfer taking place on Al–Cu surface a selection of adequate substances or technological parameters inhibiting this reaction may find an application in elaboration or modifying of surface technology. In this work the particular technological steps of the complex electrophosphating process of AA2017 were elaborated using results obtained from voltammetric transients. It was shown that a partial removal of Cu from the surface without affecting bulk content was the most effective de-smutting stage while inhibitors of Al/Cu corrosion were effective in the post-treatment stage.